Case file: rotavirus gastroenteritis in the older adult (Horizontes de Enfermería, 2019)
Acute diarrheal disease caused by rotavirus in older adults is rare, and therefore its incidence in Ecuadorian population it is not well known; cases usually occur after contact with pediatric patients or travelers, the characteristics of this pathology are very similar to those caused by other viral agents. With geriatric patients, the diarrheal syndrome caused by rotavirus can cause severe cases of dehydration and multi systemic involvement, which added to the presence of comorbidities, geriatric patients may require hospitalization. The case report of an 86-year-old male patient that comes to the emergency room with diarrhea, signs of dehydration and flu, is presented, who after performing the stool immunochromatographic test was diagnosed with rotavirus. In this article we will analyze this viral infection in the elderly.
Keywords: Diarrheic Disease; Rotavirus; Elderly